More with document work, less with patient care: An institutional ethnography of discharge planning practices for diabetic patients - Titis Kurniawan, S.Kep., Ners., MNS; Kittikorn Nilmanat; Umaporn Boonyasopun; Amelia Ganefianty (Jurnal Keperawatan Padjadjaran, 2024)
Background: Diabetic patients required comprehensive discharge planning. However, this is a complex and challenging process. Nurses play significant roles and experience tensions in operating the everyday discharge planning practices. Purpose: to explore how nurses’ everyday activities in providing DP for diabetic patients were regulated by the ruling relations operating in the hospital as an institutional context. Methods: This institutional ethnography study applied phone-call interviews with 18 participants, participant observation, and document review to collect the data. Data analysis was concurrently conducted with the data collection processes following the institutional ethnography analytical approach. Trustworthiness was established. Results: The everyday discharge planning practices for diabetic patients follow the flow of patient care. Nurses perceived these practices to be problematic as the initial assessment form did not guide the discharge education, which was informal and unstructured, and documentation was burdensome. The hospital accreditation, nurse ward manager, and the registered nurse were identified as the ruling relations that regulate those practices through the hospitals’ standards and forms, monitoring, and completeness principle. Conclusion: The hospital’s forms, monitoring, and completeness principles are activated as the ruling relation that regulates the discharge planning practices for diabetic patients for satisfying good hospital service quality through standards and forms, monitoring, and completeness principles. This situation drives nurses to work more closely with the documents. Further study is crucial to identify a strategy to effectively bridge discharge planning practices and documentations works.